Students' Perceptions of Using Duolingo Application in Speaking Skills - Sakina, Rahma; Kulsum, Eva Meidi; Siti Hardiani, Putri (Ma'soem University, 2025)
Speaking is an important skill that students must have when learning a language, particularly English. With increasingly advanced or modern developments, some applications can help in learning English, particularly speaking skills, such as the Duolingo application. This research explores students’ perceptions of grade 11 science students at SMAN 1 Rancaekek on the use of Duolingo application in learning speaking, its advantages and disadvantages. To collect the data, a questionnaire adapted from Utami, D. Y, (2020) and Inayah, N., et. al (2020) was given to twenty students and interview was addressed to nine students. The finding reveals that students have a positive perception to the use of the Duolingo application in speaking skills. Moreover, the findings show that there were five advantages, including increasing students’ motivation and encouraging students’ independence in learning speaking skill, assisting students in learning process, adding students’ understanding of English pronunciation, and improving students’ speaking skill. Meanwhile, research identifies three main drawbacks of using Duolingo for speaking skills: it requires an internet connection, includes distracting advertisements, and demands substantial storage space, all of which may hinder its effectiveness in speaking practice. Therefore, it is hoped that this research can provide benefits for students by using the Duolingo application to practice and improve their English learning process and speaking skills.